Performance of the Environmental and Forestry Office through the 'Zero Waste' Program in Polewali Mandar Regency, West Sulawesi Province - ayu achriany sopian; dwi agus sumarno; Herson simbolon (Journal of Research in Social Science and Humanities, 2024)
The amount of waste generated in Polewali Mandar Regency in 2022 was 2,852,712 tons from a population of 488,857, indicating that the waste management by the Department of Environment and Forestry, which is responsible for waste issues in Polewali Mandar Regency, is not yet optimal. Meanwhile, Government Regulation No. 97 of 2017 Article 5 paragraph 1 concerning the National Strategy Policy for Household Waste Management and Similar Household Waste targets a waste generation rate of 30%. Therefore, this research aims to identify and describe the performance of the DLHK through the Zero Waste program, the inhibiting factors, and the efforts in waste management in Polewali Mandar Regency. This thesis research uses qualitative descriptive research with an inductive approach. The data collection techniques used by the researcher are interviews, observations, and documentation. The data analysis techniques used in this thesis research consist of data reduction, data presentation, and conclusion drawing or verification. According to Soesilo's theory (Nogi, 2005), the results of this study conclude that in waste management, the performance of the DLHK through the "Zero Waste" Program has made a positive contribution to maintaining cleanliness. However, the limitations of the study include: first, the research only uses a qualitative approach with interview techniques, which are not yet able to predict which dimensions and indicators most influence the measurement of the performance of the Department of Environment and Forestry through the "Zero Waste" program in Polewali Mandar Regency, West Sulawesi Province. Second, the limitation of data collection time and the interviews conducted are subjective, depending on the informants' memory and perceptions, which affects the accuracy and reliability of the data. Third, this study has not explained other factors influencing performance, such as the role of regional leadership like sub-district heads and village heads, which are indicated to play a role in taking over these tasks and responsibilities..Keywords: Performance, Waste Management, waste generation.